Patient- and Community-Oriented Primary Care Approaches for Health in Rural, Remote and Resource-Dependent Places: Insights for Eco-Social Praxis - Buse, Chris G.; Allison, Sandra; Cole, Donald C.; Fumerton, Raina; Parkes, Margot Winifred; Woollard, Robert F. (Frontiers in Public Health, 2022)
Accelerating ecological and societal changes require re-imagining the role of primary care and public health to address eco-social concerns in rural and remote places. In this narrative review, we searched literatures on: community-oriented primary care, patient-oriented research engagement, public health and primary care synergies, and primary care addressing social determinants of health. Our analysis was guided by questions oriented to utility for addressing concerns of social-ecological systems in rural, remote contexts characterized by a high degree of reliance on resource extraction and development (e.g., forestry, mining, oil and gas, fisheries, agriculture, ranching and/or renewables). We describe a range of useful frameworks, processes and tools that are oriented toward bolstering the resilience and engagement of both primary care and public health, though few explicitly incorporated considerations of eco-social approaches to health or broader eco-social context(s). In synthesizing the existing evidence base for integration between primary care and public health, the results signal that for community-oriented primary care and related frameworks to be useful in rural and remote community settings, practitioners are required to grapple with complexity, durable relationships, sustainable resources, holistic approaches to clinician training, Indigenous perspectives, and governance.